2019
DOI: 10.1080/00218464.2019.1685384
|View full text |Cite
|
Sign up to set email alerts
|

On stickiness of multiscale randomly rough surfaces

Abstract: We derive a very simple and effective stickiness criterion for solids having random roughness using a new asymptotic theory, which we validate with that of Persson and Scaraggi and independent numerical experiments. Previous claims that stickiness may depend on small scale quantities such as rms slopes and/or curvatures, obtained by making oversimplified assumptions on the contact area geometry, are largely incorrect, as the truncation of the PSD spectrum of roughness at short wavelengths is irrelevant. We fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 48 publications
5
22
0
Order By: Relevance
“…Actually, the present results reinforce the growing consensus that extremely accurate measurement of roughness should not be needed but it is the long wavelength content of roughness which matters most [1][2][3][4][5]. While Dalvi et al [13] have used a more precise calculation of the roughnessinduced increase of area A true ∕A 0 which indeed seems to improve the correlation with experiments that they reported, it remains true that the role of A true ∕A 0 seems insufficient to explain adhesion enhancement, and that the Guduru effect (which is still not entirely understood for random roughness), has some chance in explaining the adhesion enhancement.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Actually, the present results reinforce the growing consensus that extremely accurate measurement of roughness should not be needed but it is the long wavelength content of roughness which matters most [1][2][3][4][5]. While Dalvi et al [13] have used a more precise calculation of the roughnessinduced increase of area A true ∕A 0 which indeed seems to improve the correlation with experiments that they reported, it remains true that the role of A true ∕A 0 seems insufficient to explain adhesion enhancement, and that the Guduru effect (which is still not entirely understood for random roughness), has some chance in explaining the adhesion enhancement.…”
Section: Discussionsupporting
confidence: 86%
“…-The Dalvi variant of PT criterion [13] where and h ′ rms is evaluated from ((5), second equation) 5 ; -The modified version of the Guduru model (10) proposed in the present paper.…”
Section: Pt Variants and A Modified Form Of The Guduru Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…which is convergent for H ≥ 0.5. This convergence of ⁎ γ is similar to the conclusions found in references [32][33][34][35][36][37][38] and in contrast with work done in refs. 39,40 .…”
Section: Pull-off Force and Scaling Besides Jump To Contact Instabilsupporting
confidence: 92%
“…Adhesion is a challenging topic in tribology [1][2][3] with relevance in several engineering applications that range from biomimetics [4], soft matters [5], soft robots [6], grippers [7], friction [8][9][10][11][12]. Although roughness is usually responsible for adhesion reduction [13][14][15], Briggs and Briscoe [16] showed already in 1977 that relatively small random roughness amplitude could enhance adhesion in pull-off experiments as well as relative rolling resistance by a factor up to 2.5. Later, Guduru [17] showed that in the contact between a rigid sphere and a soft halfspace with an axisymmetric single wavelength waviness, adhesion could be enhanced by a factor up to 20 with respect to the Johnson-Kendall-Roberts smooth case ( [18], JKR in the following).…”
Section: Introductionmentioning
confidence: 99%